Reversing Ongoing Chronic Intestinal Inflammation and Fibrosis by Sustained Block of IL-12 and IL-23 Using a Vaccine in Mice. Issue 9 (17th May 2018) - Guan, Qingdong; Weiss, Carolyn R; Wang, Shuhe; Qing, Gefei; Yang, Xi; Warrington, Richard J; Bernstein, Charles N; Peng, Zhikang
Abstract: Interleukin (IL)-12 and IL-23 that share subunit p40 are important cytokines in the pathogenesis of inflammatory bowel disease. We reported that mouse p40 peptide-based vaccines ameliorated intestinal inflammation in the prevention of trinitrobenzene sulfonic acid (TNBS)–induced murine colitis model. Here, we evaluated whether administration of the vaccine after establishment of colitis would be effective in modifying both TNBS-induced and dextran sulfate sodium (DSS)–induced chronic colitis and the underlying immune mechanisms. We further examined whether vaccination could exacerbate infections. Chronic colitis was developed by either intrarectally administrating TNBS or drinking 4% DSS water. Vaccination started after two TNBS administrations or 7 days of DSS treatment. Results showed that administrating p40 vaccine induced high tittered antibodies to IL-12 and IL-23, improved clinical scores, reduced intestinal inflammation and fibrosis, and down-regulated proinflammatory cytokine productions in colon tissue, compared with control mice. Furthermore, in lamina propria mononuclear cells and/or mesenteric lymph nodes, mice immunized with p40 peptide vaccine exhibited high ratios of Treg/Th1 and Treg/Th17 cells and increased IL-10 expression in CD11c + IL-10 + cells. In mice infected with lung chlamydia, in which the protective role of Th1/Th17 is well documented, vaccine immunization did not increase lung bacterial burden. We conclude that p40 vaccine may provide a potential and safe approach for treatment of IBD. :